Characterisation of Thinopyrum bessarabicum chromosomes through genome-wide introgressions into wheat - Grewal, Surbhi; Yang, Caiyun; Hubbart Edwards, Stella; Scholefield, Duncan; Ashling, Stephen; Burridge, Amanda; King, Ian P.; King, Julie (Springer, 2018)
Thinopyrum bessarabicum (2n = 2x = 14, JJ) is an important source for new genetic variation for wheat improvement due to its salinity tolerance and disease resistance. Its practical utilisation in wheat improvement can be facilitated through development of genome-wide introgressions leading to a variety of different wheat–Th. bessarabicum translocation lines. In this study, we report the generation of 12 such wheat–Th. bessarabicum recombinant lines, through two different crossing strategies, which were characterized using sequential chromosome single colour and multi-colour genomic in situ hybridization (sc-GISH and mc-GISH), multi-colour fluorescent in situ hybridization (mc-FISH) and single nucleotide polymorphic (SNP) DNA markers. We also detected 13 lines containing different Th. bessarabicum chromosome aberrations through sc-GISH. Through a combination of molecular and cytological analysis of all the 25 lines containing Th. bessarabicum recombinants and chromosome aberrations we were able to physically map 1150 SNP markers onto seven Th. bessarabicum J chromosomes which were divided into 36 segmental blocks. Comparative analysis of the physical map of Th. bessarabicum and the wheat genome showed that synteny between the two species is highly conserved at the macro-level and confirmed that Th. bessarabicum contains the 4/5 translocation also present in the A genome of wheat. These wheat–Th. bessarabicum recombinant lines and SNP markers provide a useful genetic resource for wheat improvement with the latter having a wider impact as a tool for detection of introgressions from other Thinopyrum species containing the J or a closely-related genome such as Thinopyrum intermedium (JrJrJvsJvsStSt) and Thinopyrum elongatum (EeEe), respectively.